Zebrafish as a tool to study schizophrenia-associated copy number variants - Philip D. Campbell; Michael Granato (The Company of Biologists, 2020)
Schizophrenia remains one of the most debilitating human neurodevelopmental disorders, with few effective treatments and striking consequences felt by individuals, communities and society as a whole. As such, there remains a critical need for further investigation into the mechanistic underpinnings of schizophrenia so that novel therapeutic targets can be identified. Because schizophrenia is a highly heritable disorder, genetic risk factors remain an attractive avenue for this research. Given their clear molecular genetic consequences, recurrent microdeletions and duplications, or copy number variants (CNVs), represent one of the most tractable genetic entry points to elucidating these mechanisms. To date, eight CNVs have been shown to significantly increase the risk of schizophrenia. Although rodent models of these CNVs that exhibit behavioral phenotypes have been generated, the underlying molecular mechanisms remain largely elusive. Over the past decades, the zebrafish has emerged as a powerful vertebrate model that has led to fundamental discoveries in developmental neurobiology and behavioral genetics. Here, we review the attributes that make zebrafish exceptionally well suited to investigating individual and combinatorial gene contributions to CNV-mediated brain dysfunction in schizophrenia. With highly conserved genetics and neural substrates, an ever-expanding molecular genetic and imaging toolkit, and ability to perform high-throughput and high-content genetic and pharmacologic screens, zebrafish is poised to generate deep insights into the molecular genetic mechanisms of schizophrenia-associated neurodevelopmental and behavioral deficits, and to facilitate the identification of therapeutic targets.